Zur Kenntnis einiger palaearktischer Arten der Gattung Asyndetus Loew (Diptera: Dolichopodidae). - Negrobov, O. P. (Contributions to Entomology = Beiträge zur Entomologie, 1973)
In this paper 18 palaerctic species of the genus Asyndetus Loew, 1869 are listed and includet in a key. The descriptions of three species are enlarged, and three new species are described. A key for distinguishing the genera Cryptophleps Lichtwardt and Asyndentus Loew is suggested, and Asyndetus is described in detail. Nomenclatural Actsanticus Negrobov, 1973 (Asyndetus), spec. n.izius Negrobov, 1973 (Asyndetus), spec. n.longicornis Negrobov, 1973 (Asyndetus), spec. n.